EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK ORIENTASI KARIR STUDI LANJUT SISWA DI SANGGAR BIMBINGAN KEPONG - Lubis, Maudi Alwani Akmal; M. Fauzi Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine whether group counseling at the Kepong Guidance Center improves students' career orientation. Final-year students need to have a strong career orientation to prepare themselves for further education. Using a one-group pretest-posttest pre-experimental design, this study employed a quantitative methodology. The research population consisted of eight students—five from Grade V and three from Grade VI—who were all enrolled at the Kepong Guidance Center. Total sampling was the method used, meaning the research sample included the entire population. A validated career orientation scale was used as the research instrument. With a t-value of 4.372, which is greater than the critical t-table value of 2.365 at a 0.05 significance level, the results indicate a substantial increase in students' career orientation scores after the group counseling sessions. The average score increased from 65.25 to 82.75, reflecting a 26.8% improvement in the effectiveness of group counseling. It is evident that students at the Kepong Guidance Center benefit from group counseling in terms of their career orientation.